1994
DOI: 10.5144/0256-4947.1994.326
|View full text |Cite
|
Sign up to set email alerts
|

Use of Blood in Elective Surgery: An Area of Wasted Hospital Resource

Abstract: Unavailability of blood is a common cause of canceled operations but clinicians' blood ordering habits have been shown to waste hospital resources. A prospective audit was set up in a blood bank in a teaching hospital in Saudi Arabia. Data were separately logged on blood transfusion for all surgical operations between August 1991 and December 1992. Standard terminology was employed. During the 16 months, 565 consecutive operations were logged. Only two of eight departments met the criterion of efficient blood … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 7 publications
0
18
0
Order By: Relevance
“…A value of 0.5 or more is suggestive of efficient blood usage. 20 The present study reported a TI value of 0.87. Ebose and Osalumese reported a TI of below 0.5.…”
Section: 910mentioning
confidence: 71%
“…A value of 0.5 or more is suggestive of efficient blood usage. 20 The present study reported a TI value of 0.87. Ebose and Osalumese reported a TI of below 0.5.…”
Section: 910mentioning
confidence: 71%
“…It has been reported that only 30% of cross-matched blood is used in elective surgery. [8] Therefore, it is essential that the usage of blood and blood products should be rationalised and saved for critical situations. [7] According to this recommendation, the cross-match to transfusion ratio of 1.010 that is reported in the current study indicates efficient blood usage.…”
Section: Department-wise Distribution Of Demand and Issuementioning
confidence: 99%
“…Blood banks face an everincreasing demand for blood and its components. It has been reported that only 30% of crossmatched blood is used in elective surgery [3]. In a report by Mwambungu et al in 2015, only 64% of crossmatched blood was utilized [4].…”
Section: Introductionmentioning
confidence: 99%